2013
DOI: 10.5152/ttd.2013.18
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Success of Smoking Cessation

Abstract: ÖzetAMAÇ: Sigara icen bir kijinin sagliginin korunmasi için yapilmasi gereken en önemli |ey sigaranin birakilmasidir. Bu çali §mada; Abstract sigara birakma programma alman hastalarda sigarayi birakmada etkili olan faktörlerin ve uygulanan tedavi yöntemlerinin etkisini degerlendirmeyi planladik. GEREÇ VE YÖNTEMLER:Sigara birakma poliklinigine baçvuran 400 olgu retroprospektif olarak çaliçmaya aimdi. Olgularm 3. ay sonu tedavi sonuçlarmm degerlendirilmesi planlandi. Olgularm demografik özellikleri, sigara içme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
25
1
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 12 publications
(13 reference statements)
4
25
1
8
Order By: Relevance
“…While in some studies examining the effect of education level on the success of smoking cessation it was reported that in the groups having a high level of education, the rate of smoking cessation is high (20,21), there was no difference found between quitting smoking and different education levels (9,14). In our study, there was no difference between the groups quitting smoking and those not being able to quit smoking with regard to the education level.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…While in some studies examining the effect of education level on the success of smoking cessation it was reported that in the groups having a high level of education, the rate of smoking cessation is high (20,21), there was no difference found between quitting smoking and different education levels (9,14). In our study, there was no difference between the groups quitting smoking and those not being able to quit smoking with regard to the education level.…”
Section: Discussioncontrasting
confidence: 62%
“…In other studies conducted in our country, smoking cessation success at the end of the first year changes between 21% and 48% (8)(9)(10)(11)(12)(13). Studies investigating the effects of sociodemographic factors, additional diseases and the characteristics of smoking on smoking cessation success were carried out and it was reported that smoking cessation success is related with age, gender, socioeconomic status and nicotine dependence (14-17).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Success rates reported for all groups ranged from 21.6 to 43.7%. Ten percent of patients resumed smoking after finishing their therapy (14)(15)(16)(17)(18). All pharmacological therapies seem successfull in the short-term, but their long-term effects are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Yeterli uyku, egzersiz, sağlıklı yiyecekler ile dengeli beslenme, stres topu, nefes egzersizleri, yoga veya kişilerin kendilerine iyi gelen kendi keşfettik-leri uğraşlarla gevşeme ve stresi azaltma çabaları iyi gelecektir. Sıcak bir banyo, yeni bir kitap, seyretmek istediği bir film hem gevşeme hem de sigara içme isteklerine iyi gelecektir (Tablo1) (9,10) .…”
unclassified